MENURUNKAN TINGKAT REJECT DI LINE BASS STRING PADA PRODUK WIRESTRING PIANO MENGGUNAKAN METODE FTA DAN FMEA DI PT. YAMAHA INDONESIA - ramadhan purba, depki; Kurnia, Ismail; Nurhasan Assidiq, M (Universitas Krisnadwipayana, 2024)
PT. Yamaha Indonesia is a Japanese manufacturing company that is involved in piano production. Most of the pianos produced by PT. Yamaha Indonesia, namely upright pianos as much as 83.94%, while grand pianos as much as 16.06% of the total production. The piano that is produced consists of several parts in it. One of the parts that support the piano produced by PT. Yamaha Indonesia is wirestring. In this study we will use the Failure Mode and Effect Analysis (FMEA) method. After analyzing the biggest cause of rejection of wire string products in the BassString line is caused by material factors where the tuning pinfor the wire string tightening process often causes the reject is loose, after repairs and replacement of thetuning pin with the rings are proven to reduce the occurrence of reject products on the wire string in the bass string line. with the initial actual reject data of 7.7% reduced to 5% in the first month of repair done, with this it can be concluded that research on wire string products has succeeded in reducing the percentage of rejects.